Pheochromocytoma in a Dog as a Cause of Aortic Thromboembolism - Marcasso, Rogério A.; Arias, Mônica V. Bahr; Gianini, Luciana; Headley, Selwin A.; Bracarense, Ana Paula.F.R.L. (Brazilian Journal of Veterinary Pathology, 2011)
A thirteen-year-old female German Spitz dog was referred to Veterinary Hospital of the Universidade Estadual de Londrina, with acute paraplegia and pain in pelvic limbs for two days. The clinical sings, as lack of femoral pulse and cold distal limbs, were consistent with ischemic neuromyopathy due to aortic thromboembolism. Soon after the examination, she had a severe epistaxis and died. On postmortem examination it was observed a thrombus adhered to the aorta trifurcation and a mass occupying the position of the right adrenal gland, which was diagnosed as pheochromocytoma on histological and immunohistochemistry examinations.